2011
DOI: 10.1111/j.1095-8312.2011.01804.x
|View full text |Cite
|
Sign up to set email alerts
|

On the association between environmental gradients and skull size variation in the great fruit-eating bat, Artibeus lituratus (Chiroptera: Phyllostomidae)

Abstract: Understanding the spatial distribution of phenotypes and their association with local environmental conditions can provide important insights into the evolutionary history and ecological dynamics of species. Geographical variation in the skull size of the Artibeus lituratus complex was explored to evaluate the association between morphological traits and habitat-specific environmental conditions in the mainland populations of Middle and South America. We performed a principal component analysis based on 390 mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 47 publications
0
25
0
3
Order By: Relevance
“…Thus, bats living in such environments are more likely to be smaller . Additionally, Burnett (1983) found that precipitation had a greater influence on wing and skull size of E. fuscus than did the temperature, while Marchán-Rivadeneira et al (2012) reported that skull size in A. lituratus increased as the amount of precipitation during the driest season increased. On the other hand, we found that four climatic factors related to temperature have statistically significant effects on the skull size variation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Thus, bats living in such environments are more likely to be smaller . Additionally, Burnett (1983) found that precipitation had a greater influence on wing and skull size of E. fuscus than did the temperature, while Marchán-Rivadeneira et al (2012) reported that skull size in A. lituratus increased as the amount of precipitation during the driest season increased. On the other hand, we found that four climatic factors related to temperature have statistically significant effects on the skull size variation.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, genetic differentiation and differences in genetic variability between isolated populations probably reflect the species' colonization history and also point to reduced gene flow over greater distances (Rossiter et al, 2006). Study of association of phenotype variation with local environmental conditions can provide important insights into the evolutionary history and ecological dynamics of particular species (Marchán-Rivadeneira et al, 2012). The local environmental conditions can induce marked phenotypic differences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In isolated areas, such as islands, bats may exhibit dwarfism in comparison with their continental counterparts (Case, 1978) in its morphological characters (Caumul and Polly, 2005;Evin et al, 2011;Marchán-Rivadeneira et al, 2012). The Baja Cali fornia group fits this pattern as a group with geographical isolation.…”
Section: Geometric Morphometricsmentioning
confidence: 82%